Pengaruh Teknik Perlakuan Pascapanen terhadap Karakteristik Buah Mangga cv. Gedong - Mulyawanti, Ira; Setyawan, Nurdi; Setyabudi, Dondy Anggono (Jurnal Hortikultura Indonesia, 2020)
Disease attack due to fungi or insects is one of the problems in storing mangoes. Techniques to suppress the development of existing postharvest diseases include hot water treatment (HWT), waxing, or the use of chemicals such as fungicides and insecticides. The treatment can suppress the development of postharvest mango, but on the other hand, the use of high temperatures and chemicals affect the physiological activity and sensory of the fruit after storage. The study aimed to evaluate the effect of preliminary treatment before storage on the quality of mangoes. Mangoes were treated with HWT, waxing and dipping in galangal extract, then packaged and stored at cold temperatures (9 °C) for 28 days in a refrigerated container length 609.6 cm. Characteristics of mangoes observed include texture, color, total soluble solids, vitamin C, maturation and demonstration time, and the type of damage in each treatment. The results showed that the immersion treatment in galangal extract gave the best result in increasing the shelf life of mango cv. Gedong and maintaining the physiological quality of the fruit.